2007
DOI: 10.1186/1476-7120-5-27
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic quantification of myocardial function using tissue deformation imaging, a guide to image acquisition and analysis using tissue Doppler and speckle tracking

Abstract: Recent developments in the field of echocardiography have allowed the cardiologist to objectively quantify regional and global myocardial function. Regional deformation (strain) and deformation rate (strain-rate) can be calculated non-invasively in both the left and right ventricle, providing information on regional (dys-)function in a variety of clinical settings. Although this promising novel technique is increasingly applied in clinical and preclinical research, knowledge about the principles, limitations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
251
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(263 citation statements)
references
References 33 publications
2
251
0
10
Order By: Relevance
“…Both techniques rely on different principles to calculate both regional and global deformation and deformation rate. We have previously shown that both techniques are feasible in the RV and that the calculated values are comparable to one another in ARVD/C patients [18].…”
Section: Tissue Deformation Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Both techniques rely on different principles to calculate both regional and global deformation and deformation rate. We have previously shown that both techniques are feasible in the RV and that the calculated values are comparable to one another in ARVD/C patients [18].…”
Section: Tissue Deformation Imagingmentioning
confidence: 99%
“…Emerging new echocardiographic techniques, specifically three dimensional (3D) RV echocardiography and tissue deformation imaging, may increase the performance of echocardiography, overcoming the previously mentioned shortcoming of conventional RV echocardiography [17,18]. 3D imaging enables more accurate RV volumetric measurements compared to conventional echocardiography [19,20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The recent development of twodimensional (2D) speckle tracking echocardiography (STE) overcomes some of these limitations and its superiority to Doppler strain has been demonstrated [8]. This new echocardiographic approach allows the objective evaluation of both regional and global systolic and diastolic functions of myocardium in detail.…”
Section: Introductionmentioning
confidence: 99%
“…RV volume measurements by 2D echocardiography correlate poorly with CMR [1]. Strain and strain-rate imaging provides an accurate, yet indirect, assessment of RV myocardial performance [2]. Three-dimensional echocardiography provides more accurate RV volume measurements than 2D echocardiography, yet compared with CMR it consistently underestimates RV volume [3][4][5].…”
mentioning
confidence: 99%